The evaluation of the implementation of regional autonomy in Indonesia - Rudy Badrudin; Baldric Siregar (Universitas Islam Indonesia, 2015)
The implementation of regional autonomy has been running nearly 15 years. In fact, the purpose of regional autonomy for improving the welfare has not been fully achieved. This study aims to evaluate the implementation of regional autonomy in improving the welfare by using capital expenditure and growth as an intervening variable. We use the data of 461 counties and cities, the period of 2006-2013, Partial Least Square for testing hypotheses. Empirical evidence shows that decentralization significantly effect on capital, growth, and welfare. Capital has a significant effect on growth but does not has a significant effect on welfare. Growth has a significant effect on welfare.